PANCASILA DALAM SUDUT PANDANG STUFENBAUTHEORIE - Suryani Yusi; Sentot Supriyadi (Justici, 2020)
Abstract If a country wants to stand strong and strong, surely it must have a strong and solid state ideology as the basic and basic norms of the country. Without it, the nation and state will be fragile because they do not have a handle. The basic norm is the crystallization of the values ​​that live in a country that can be able to glue the unity of unity for a nation and state, while the foundation of the state is the foundation for a country. The basic and basic norm of the State in Indonesia is Pancasila.